Learning from each other: Latin America and Senegal exchange innovative climate approaches for smallholder farmers - Howland, Fanny C.; Bonilla Findji, Osana; Loboguerrero Rodriguez, Ana María; Peterson, Caitlin (2016)
Smallholder farmers in the developing world are particularly vulnerable to the impacts of climate fluctuations and weather extremes. While these farming communities have survived by mastering the ability to adapt to an increasingly uncertain climate, their indigenous knowledge and traditional coping practices has been overwhelmed. Supporting farmers with effective weather and climate information and advisory services for agricultural decision making is a key strategy for reducing risk and enhancing food security in already vulnerable areas. However, broadening the impact of climate services in vulnerable communities has been a challenge. Several initiatives in Sub-Saharan Africa and Latin America have used innovative approaches to overcome these challenges. By communicating and applying seasonal forecast information in these two regions through pilot-scale projects, they demonstrate good practice and provide valuable insights such as it has been evidenced in Senegal.